Processing tomato in the sub-middle São Francisco valley and the pests limiting its production. - Filho, Francisco Lopes (Pesquisa Agropecuaria Brasileira, 2014)
In this paper the economic importance, the best planting period and the main pests limiting the tomato crop production in the Sub-Middle São Francisco region are reported. The pests are: Scrobipalpula absoluta (Meyrick, 1917); Aculops lycopersici (Massée, 1937); Tetranychus evansi (Baker & Pritchard, 1960); Heliothis zea (Bod, 1850) and Pseudoplusia oo (Cramer, 1782); Liriomyza sativae (Blanchard) and Agrotis ipsilon (Hufnagel, 1776